Synthesis and Characterisation of Banana-shaped Liquid Crystal Compound Derived from Isophthalic Acid as a Central Core - Tamilenthi2, Sreehari Sastry3, Sandy Subala1, Syama Sundar1, V.Padmini (Recent Research in Science and Technology, 2011)
The synthesis and mesomorphic properties of a homologous series of schiff’s base bent core liquid crystal compounds are reported. Two amino groups are connected to a central part isophthalic acid bis(4-formyl-phenyl)ester. The terminal alkoxy chains have been varied from 4 to 11 and 16 carbon atoms in length. All the compounds exhibit liquid crystalline phases which were stable in nature. Only the A-16 compound show a show nematic phase along with B1 phase. All the synthesized nine compounds exhibited enantiotropic liquid crystal phase. The transition temperatures and phase behaviours were studied by Differential Scanning Calorimetry (DSC), Polarizing Optical Microscopy (POM).